QoE-Based Performance Evaluation for Adaptive Media Playout Systems - Mingfu Li (Advances in Multimedia)
To improve the playout quality of video streaming services, several adaptive media playout (AMP) mechanisms were proposed in literature. However, all performance evaluations and comparisons for AMPs were made in terms of quality of service (QoS) metrics. As one knows, there may exist a trade-off between QoS metrics, such as buffer underflow and overflow performance. Thus, it is not sufficient to only evaluate the performance of AMPs in terms of QoS metrics. In this paper, we will evaluate and compare the performance of several AMPs from the aspect of quality of experience (QoE). Numerical results will show that some existing AMP systems do not perform better than the nonadaptive playout system from the point of view of overall QoE.